Monodispersed Iron Selenide Nanoparticles United with Carbon Nanotubes for Highly Reversible Zinc–Air Batteries - Hua Zhang; Tong Zeng; Jiale Ma; Yue Jiang; Yang Huang; Yuxin Cheng; Haifeng Ye; Cuiyun Zeng; Chenghui Zeng; Minshen Zhu; Shuiliang Chen (Small Structures)
Developing electrocatalysts that exhibit exceptional activity without relying on noble metals, all while ensuring high efficiency and durability for the oxygen reduction and evolution reactions, poses a challenging yet highly desired task. Monodispersed nanoparticles on a conductive framework through strong metal–support interactions are known to show excellent catalytic performance. Herein, monodispersed iron selenide embedded in a carbon nanotube network is synthesized. Graphitic carbon shells enclosing monodispersed iron selenide address the primary challenge of nanoparticle catalysts—aggregation and corrosion of nanoparticles over repeated oxygen redox reactions. By amplifying the interaction of Fe with carbon nanotubes, the heterogeneous catalyst forms highly active centers for oxygen redox reaction from the coordinated iron atoms, along with conductive iron–nitrogen–carbon nanotube pathways for rapid charge transfer. As a result, the heterogeneous catalyst exhibits superior activity for both oxygen reduction (E1/2 = 0.88 V) and oxygen evolution (η = 360 mV@10 mA cm−2) and excellent stability of negligible degradation over 5000 cycles. The overall catalytic performance surpasses the noble metals. Therefore, rechargeable zinc–air batteries using the heterogeneous catalyst exhibit a high power density of 130.9 mW cm−2, excellent round‐trip efficiency of ≈70%, and cycling stability for over 1100 h at 10 mA cm−2.